José Marques de Melo e os estudos científicos da folkcomunicação - Gobbi, Maria Cristina [UNESP]; Fernandes, Guilherme Moreira (My University, 2013)
This paper aims some academic contributions of José Marques de Melo for the study and propagation of Folkcomunication Theory, developed by Luiz Beltrão, in 1967, in his PhD thesis. Marques de Melo, disciple of Beltrão, is one of the most representative names on the set of international scientific studies of communication. Divided in three parts, this text covers theoretical contributions (conception and classification of genders, formats and types of taxonomy of Folkcomunication); dialogues with other thinkers (McLuhan, Morin and Freire) and empirical contribution (internet as a Folk tool). We emphasize that the contributions of Marques de Melo are fundamentals for the new generations to understand the importance of the Folkcomunication and see it as a complex communicational system.

Este trabalho aponta algumas contribuições acadêmicas de José Marques de Melo para o estudo e a divulgação da Teoria da Folkcomunicação, desenvolvida por Luiz Beltrão, em 1967, em sua tese de doutorado. Marques de Melo, discípulo de Beltrão, é um dos nomes mais representativos no cenário internacional dos estudos científicos da comunicação. Dividido em três partes, esse texto abrange contribuições teóricas (a concepção e classificação dos gêneros, formatos e tipos da taxionomia da Folkcomunicação); diálogos com outros pensadores (McLuhan, Morin e Freire) e contribuições empíricas (a internet como ferramenta Folk). Ressaltamos que as contribuições de Marques de Melo são fundamentais para as novas gerações compreenderem a importância da Folkcomunicação e percebê-la como um complexo sistema comunicacional.
José Marques de Melo and scientifics studies about folkcomunicacion
Keywords: Folkcomunicacion; Internet; Latin American; Luiz Beltrão; José Marques de Melo; Folkcomunicação; Internet; América Latina; Luiz Beltrão; José Marques de Melo